Jogásztársadalom a globalizáció tükrében - Nagy Zsolt (Szegedi Tudományegyetem Állam- és Jogtudományi Karának tudományos bizottsága Szeged, 2006)
In the past 30 years in the United States or in Europe and even in the global world the social changes have had great affect on the law society and perhaps on the legal education as well. Before the '70s it was thought that the aspiring lawyers should have been taught and the lawyres should have been know the nuances of the common law and proper pleading, or the positive text of law and some kind of methods of interpretation of those text on the national basis. But from that time and nowadays these ideas have changed. As a consequence of the social and economical turning it is unimaginable for several lawyers to organise their work on this national basis any more. So many law firms have begun to organise their work on an international basis by the astabli§hrnent of branch offices around the world. These trends led to the rise of Mega-Lawyering and the Multidisciplinary Practice. I have attemted to set forth these trends nowadays and in the future trough two tales: on the one hand the tale of the Canadian lawyer's society on the other hand the tale of the Australian lawyers. At the end of the histories the final most important conclusion is that the lawyers (and the people as well) do not think about the law not merely as the device of juctice or the ability of calculation by doctrines and common sense but they think about it as just a device with they can win an intellectual battle in the global world.
Keywords: Társadalomtudományok; Jogtudomány